Management of Student Requirements Data Collection for Graduation and Diploma Retrieval Activities - Sujatmiko, Sujatmiko; Sufaidah, Siti; Munawarah, Munawarah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
University of KH.. A. Wahab Hasbullah Jombang is a private university with a number of students reaching 2,300 in 2021. The large number of students demands manpower and time to provide administrative services to students. One of the student services that needs attention is the service for taking certificates and graduations which are still done manually. The purpose of this research is to make it easier for staff, prospective graduate students, and graduation committees to manage graduation activities and take certificates by utilizing digital media. This research was conducted at the University of KH. A. Wahab Habullah Jombang uses the experimental method. The development model used is the waterfall model. The test results of applications developed using the blackbox method show that the system developed is in accordance with the expected results. This means that the application developed is feasible to be applied to management activities for sending graduations and taking diplomas at University of KH.. A. Wahab Hasbullah Jombang.